Calculation of Characteristic Impedance of Multiconductor Lines - Kleiza, A.; Staras, S. (Elektronika ir Elektrotechnika, 1999)
Methods of calculation of characteristic impedance of multiconductor lines are analysed. The results of calculations using different methods are presented and discussed. The best accuracy is ensured using finite difference method. The software, automatically choosing calculation method according to given accuracy, is created.